Towards an Efficient Memory Architecture for Video Decoding Systems - Bonatto, Alexsandro C.; Negreiros, Marcelo; Soares, André B.; Susin, Altamiro A. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Multimedia applications are known to use large amounts of memory. The video modules need also high throughput memory port for coding and decoding high resolution video sequences. The design of a multimedia System-on-Chip (SoC) could implement embedded block RAMs but it is much more cost-effective to use a single external memory at the expense of a multichannel memory controller. This paper presents the design and implementation of an efficient memory hierarchy for a Set-Top Box (STB) SoC with a video decoder. To use efficiently the Double Data Rate (DDR) external memory it must be accessed in burst mode whenever possible. In this paper we develop an analysis and implementation of a four level memory hierarchy targeting data latency reduction and bandwidth optimization of the memory port. The case study is DDR2 SDRAM memory used as the main system video memory in a digital television set-top box implemented on a Virtex-5 FPGA. This paper presents the architecture of the system and shows that the memory hierarchy efficiently uses the DDR characteristics while serving four client processes. The proposed memory architecture can reduce data latency in 78% when compared to a direct demand-access procedure.